Toksisitas Fraksi Sari nHeksan Daun Kopasanda (Chromolaena odorata (L.) RM King and H. Rob) terhadap Larva Udang dengan Metode BSLT (Brine Shrimp Lethality Test) - Ayu Yolanda Ginting; Sumardi; Vierza Mierza (Jurnal Indah Sains dan Klinis, 2020)
Kopasanda leaf plants (Chromolaena odorata (L.) R.M.King & H.Rob) are plants commonly used as medicinal ingredients empirically. The people of East Aceh use it as a wound medicine. Preliminary tests show that the extract and its partitions have a toxic effect on shrimp larvae. In this study, the soluble extract of n-hexane was fractionated using column chromatography with isocratic mobile phase n-hexane: ethyl acetate (7: 3) and silica gel stationary phase. Analysis of the chemical content profile using thin-layer chromatography showed that there were polyphenol organic compounds. The fraction 7 obtained shows that it is toxic to shrimp larvae of Artemia salina Leach.